IMPROVING THE ASSESSMENT OF WRITTEN LANGUAGE SKILLS IN MIDDLE SCHOOL LEARNERS USING TRADITIONAL AND MODERN APPROACHES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This paper explores assessment methodologies applicable to evaluating the written communication of 5th–7th grade students within the framework of Uzbekistan’s ongoing educational reforms. Emphasizing both psychological and linguistic development, the study highlights effective assessment strategies, including rubric-based evaluations, self and peer-assessment, and digital tools. It demonstrates how traditional and modern approaches can be harmonized to support students’ academic writing growth while fostering creativity and critical thinking. The research provides actionable recommendations for educators aiming to improve formative and summative assessments aligned with global educational trends.